2019
DOI: 10.5530/ajbls.2019.8.3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Mucilages from Abelmoschus Manihot Linn., Amaranthus Spinosus Linn. and Talinum Triangulare (Jacq.) Willd. Leaves for Pharmaceutical Excipient Application

Abstract: Introduction: The edible leaves of Abelmoschus manihot Linn., Amaranthus spinosus Linn. and Talinum triangulare (Jacq.) Willd. are exhibiting mucilaginous features and are utilized in making soupy dishes. However, the utilization of the said plant species as sources of mucilages for pharmaceutical excipient application has not yet been reported in literatures. Objectives:The study aimed to extract and partially characterize mucilages from the leaves of A. manihot, A. spinosus and T. triangulare. for potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…There was no significant difference in the solubility between hexane and methanol. In other studies, researchers also confirmed that the mucilage was insoluble in the organic solvents [53,54]. This showed that mucilage extracted from C. olitorius L. possessed high polarity.…”
Section: Solubilitymentioning
confidence: 65%
“…There was no significant difference in the solubility between hexane and methanol. In other studies, researchers also confirmed that the mucilage was insoluble in the organic solvents [53,54]. This showed that mucilage extracted from C. olitorius L. possessed high polarity.…”
Section: Solubilitymentioning
confidence: 65%
“…345 The following reports presented general chemical composition or known compounds, but they also presented uniqueness or special interest. Betacyanins and phenolics, 346 Very detailed composition with (or without) tables, [347][348][349][350][351][352][353][354] isolation of α-spinasterol from stem extract, 355 identification and quantification of quercetin in leaves extract, 356 isolation of mucilages from leaves 357 have been reported Table 10. Biological, medicinal and other properties of Amaranthus viridis.…”
Section: Chemical Compositionmentioning
confidence: 99%